Challenges to Sustainable Tourism Marketing Operations in Zambia - Bwanga, Cynthia; Kanyamuna, Vincent (Advances in Social Sciences Research Journal, 2023)
The purpose of the study was to establish the challenges to sustainable tourism marketing in Zambia. For several years, Zambia’s economic recovery trajectory has been anchored on the travel and tourism sector. However, the industry has faced a number of challenges which among others could be attributed to the COVID-19 pandemic. The closure of borders and other travel restrictions as a result of the pandemic caused the reduction in the number of international visitors to the country. The reduction in the number of tourists have had far-reaching consequences to the sector and the economy at large. Thus, this paper sought to understand these dynamics. During this study, some of the identified challenges to the tourism sector included inadequate transformative implementation mechanisms, inadequate human resources, technical and financial resources, inadequate accommodation and transport infrastructure, limited investments, reduced international tourist arrivals, unemployment, lack of recreational activities, and inadequate tourism marketing. Arising from the challenges, it is recommended that the travel and tourism industry should be supported by financial, technical and human resources to ensure adequate implementation of the Zambia Tourism Master Plan and sustainable tourism. In addition, key stakeholders should collaborate in order to improve and construct tourism-related infrastructure, facilitate local and foreign investment into the tourism sector, encourage diversification and eco-tourism to boost tourism marketing and investment promotion in order to make the industry more lucrative and sustainable. Further, more research on the travel and tourism industry amidst the COVID-19 pandemic is recommended to provide more information for policy making and decision making in relation to the concepts of marketing research and operations research. COVID-19 exposed a lot of lacunas in the tourism sector and moving forward, Zambia would do better to ensure that policy, practice as well as legislation are supportive of a robust sector capable of thriving during pandemics.